LEGAL IMPOSSIBILITY OR INADMISSIBILITY - IS THERE A NEED FOR DISTINCTION? - Radovanović, Sanja Milan; Miščević, Nikolina B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
It is generally accepted that the origin of a contract, i.e. its validity, is influenced by an impossibility that is objective and current, regardless of whether it is legal or factual. From this distinction of possibilities according to different criteria, it follows that there is no universal determination of the possibilities of the subject. Apart from the fact that the theory relativizes possibility as a general condition of the subject of a valid contract, since it binds different legal consequences, certain provisions of the Law on Obligations also contribute to the fact that legal consequences of impossibility are not clearly defined in terms of contract validity. This is especially the case when it comes to legal impossibility. Systematic works of the law of obligations in the domestic literature speak of legal impossibility, as a special species. However, there is a lack of clear demarcation in determining what is meant by it. Therefore, we will try to re-examine whether and when the distinction between legal impossibility and inadmissibility is of practical importance.
Keywords: subject of the contract, legal impossibility of the subject of the contract, inadmissibility of the subject of the contract, binding contracts, disposal contracts.